Diagnostic delay and characterization of the clinical prodrome in AL amyloidosis among 1523 US adults diagnosed between 2001 and 2019. (23rd July 2021) - Hester, Laura L.; Gifkins, Dina M.; M. Bellew, Kevin; Vermeulen, Jessica; Schecter, Jordan M.; Strony, John; Dishy, Victor; Weiss, Brendan M.
Abstract: Light‐chain (AL) amyloidosis is a multisystem disorder with a high early mortality and diagnostic delays of >1 year from symptom onset. This retrospective observational study sought to characterize the clinical prodrome and diagnostic delay to inform early detection. We identified 1523 adults with newly diagnosed AL amyloidosis in the Optum de‐identified Clinformatics ® Datamart US healthcare claims database as those with ≥2 new diagnosis codes for AL or other amyloidosis in 90 days with ≥1 multiple myeloma treatment within 730 days, excluding patients with prior hereditary or secondary amyloidosis and Familial Mediterranean Fever. We considered 34 signs/symptoms using diagnosis codes in all observable time on or before AL amyloidosis diagnosis. Sign/symptom prevalence was compared to that of 1:4 matched population controls. The overlap and sequence of signs/symptoms and the median time from first sign/symptom to AL amyloidosis diagnosis were explored. Healthcare utilization was summarized. The most common individual AL amyloidosis signs/symptoms were malaise/fatigue (61%) and dyspnea (59%). Cardiac signs/symptoms were observed in 77% of patients, followed by renal (62%) and neurologic (59%) signs/symptoms. Multisystem involvement (≥3 systems) was present in 54%. Monoclonal gammopathy was detected in 29% before diagnosis. Median time from symptom onset to AL amyloidosis diagnosis was 2.7 years. Healthcare utilization was high between first AL amyloidosis signs/symptoms and diagnosis, with 50% visiting ≥5 physician types. AL amyloidosis patients have a lengthy and complex clinical prodrome. Novel approaches to early diagnosis are needed to improve outcomes.